UJI EFEKTIVITAS BEBERAPA LARVASIDA TERHADAP LARVA NYAMUK Aedes aegypti DARI BANJARMASIN BARAT - Istiana, Istiana (Pendidikan Dokter Universitas Lambung Mangkurat, 2015)
Dengue Haemorrhagic Fever (DHF) is a dangerous infectious disease caused by the dengue virus and is transmitted through the bite of the mosquito Aedes aegypti. DHF control depends on controlling mosquitoes and larvae. Currently larvicidal control still uses temefos, although some studies have reported the presence of resistance. Larvicides that WHO recommended as a substitute temefos is permethrin. In addition there are some new larvicides derived from the class of insect growth regulator (IGR) which contain active pyriproksifen and active ingredients methopren. This study aims to determine the effectiveness of larvicides and effective concentration to kill 50% of larvae of Aedes aegypti from the sub Banjarmasin West. This study is an experimental study design with Posttest-Only Control Group Design with permethrin dose group was 0.0015 g / l; 0.0018 g / l; 0.002 g / l; 0.0022 g / l; 0.0025 g / l; and 0.0030 g / l, for pryriproksifen use dose groups of 0.5 ppm, 0.1 ppm, 0.05 ppm, 0.01 ppm, 0.008 ppm, 0.005 ppm, and methopren with dosis0 group g / l, 0, 0063 g / l, 0.0025 g / l, 0.005 g / l, 0.01 g / l, and 0.1 g / l. Each treatment group was exposed to larvae of Aedes aegypti larvae and change shape as well as the deaths were followed for 10 days. The results showed that the effective dose of permethrin kills 50% of larvae (Lethal Concentration / LC50) 24 hours ranged from 24 hour LC50 0.01439 - 0.01829 mg / l, with an average of 0.01671 mg / l and 24-hour LC99 ranged from 0.02856 - 0.03852 mg / l with an average of 0.03196 mg / l. This study showed that the larvae of Aedes aegypti in the district of West Banjarmasin are resistant to permethrin. As for pyriproksifen larvicides effectively killed larvae by 70% after seven days of exposure, and for larvicidal with active methopren killed 50% of larvae on the eighth day. This study shows that larviciding of IGR group can be an alternative in the area that has been declared resistant to abate as in the sub-district of West Banjarmasin.Â Keywords: effectiveness, permethrin, pyriproksifen, methopren, Aedes aegypti